Effect of cinnamon (Cinnamomum bermanni) addition on antioxidant activity and organoleptic properties of moringa leaf tea (Moringa oleifera) - Nurlaila Syafitri; Veni Rori Setiawati; Jenri Parlinggoman Hutasoit (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The study aims to determine the organoleptic characteristics and antioxidant activity of the tea leaves of moringa that are added to moringa using the DPPH method. (1-difenil-2- pikrildihidrazil). This type of study is an experimental study with variations in the addition of moringa of 20 g, 30 g, 40 g, and 50 g on each treatment. Data analysis is carried out using ANOVA variance analysis at the 5% level using the SPSS software application. If there is a real effect, continue with the further Duncan test. The study results show that adding peppermint extract positively affects the tea leaves' organoleptic and antioxidant properties. The most preferred sample by the panelists for texture, color, taste, and aroma is the P4 sample (50 g of moringa + 50 g of cinnamon). Based on the antioxidant activity properties of tea leaves of moringa with the addition of moringa samples whose IC50 value is the highest is the P4 sample (50 g moringa + 50 g moringa) which is 70.55 ppm.